2013
DOI: 10.1002/term.1839
|View full text |Cite
|
Sign up to set email alerts
|

One-day treatment of small molecule 8-bromo-cyclic AMP analogue induces cell-based VEGF production forin vitroangiogenesis and osteoblastic differentiation

Abstract: Small molecule based regenerative engineering is emerging as a promising strategy for regenerating bone tissue. Small molecule cAMP analogues have been proposed as novel biofactors for bone repair and regeneration, and while promising, the effect that these small molecules have on angiogenesis, a critical requirement for successful bone regeneration, is still unclear. Our previous research demonstrated that the small molecule cAMP analogue 8-bromoadenosine-3’,5’-cyclic monophosphate (8-Br-cAMP) was able to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 48 publications
(71 reference statements)
2
13
0
Order By: Relevance
“…, Lo et al . ), and PKA activation induces in vitro osteogenesis and in vivo bone formation (Siddappa et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Lo et al . ), and PKA activation induces in vitro osteogenesis and in vivo bone formation (Siddappa et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that this signalling contributes to osteogenesis. For example, the treatment of MSCs with a cAMP stimulator results in enhanced osteoblastic differentiation (Kim et al 2013, Lo et al 2016, and PKA activation induces in vitro osteogenesis and in vivo bone formation (Siddappa et al 2008). Other studies have proposed an inhibitory role of this signalling pathway in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This coordination between timing and location of small molecules could be optimized for both specific tissue types and tissue interfaces (1). In addition, reducing the frequency of administration of small molecule drugs has been recently proposed as a promising strategy to minimize their side effects (22, 76). Nevertheless, more research work needs to be done to unravel the role of small molecules in musculoskeletal tissue regeneration prior to its clinical utility, including studying dosage requirements and effective delivery strategies (Box 3).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Thus, the ubiquitously present PDEs play a pivotal role in regulating cell signalling via the breakdown of cAMP and cGMP. PDE inhibitors are therapeutic agents which target PDE isoenzymes and inhibit the metabolism of the secondary messengers (cAMP, cGMP) thus, prolonging the biological effect determined by the type of cell involved [10,11].…”
Section: Introductionmentioning
confidence: 99%